Audio Podcast-based Learning Media in Improving Students’ Listening Comprehension and Pronunciation - Irma Rahmawati; Yohana P. Br Sianturi (Journal of Research in Business, Economics, and Education, 2021)
The study is about to improve the students listening skill and pronunciation by using podcast as one of material sources taken from the internet. The objectives of this study are to identify some steps that are going to be implemented in teaching listening and speaking using podcast to improve the students’ listening skill and their pronunciation of English Department students of Dian Nusantara University, and to analyze the effectiveness of using podcast in their learning. The researchers apply the concept of ADDIE (Analysis, Design, Development, Implementation, and Evaluation) paradigm in this study because it is more effective and systematic and supported new learning models. The participants are the fourth- semester students of English Literature students. There are two methods of collecting data in this research. They are quantitative and qualitative data. Each week, quantitative data were gathered via a series of tests, including a listening comprehension and a pronunciation examination. For qualitative data, questionnaires were used to elicit student perspectives on podcasts' effectiveness in improving listening comprehension and pronunciation. Preliminary comparative data will be gathered through a pre-test. This study uses descriptive statistical methods to analyze the data. The result is then analyzed using descriptive statistics to know the difference of scores before and after the tests. The students' ability to pronounce words has improved. The majority of the pre-test pronunciation errors are no longer present in the post-test. Furthermore, the use of podcasts as a learning medium received positive responses in the student survey. Students are encouraged to improve their listening skills because podcasts appeal to them as a learning medium.